Impact of consumption temperature and additions (milk and/or sugar) on sensory properties of hot brewed coffee - Adhikari, Jayashan (Kansas State University, 2017)
The sensory properties of coffee are impacted by various factors such as coffee origin, degree of roasting and ways of consumption. This study analyzed impact of ways of consumption (1. consumption temperatures and 2. milk and/or sugar additions) on 38 flavor attributes of hot brewed coffee by descriptive sensory analysis. Different type of coffee samples (2 Arabica, 1 Robusta, and 1 Blended) were consumed at 50ºC, 60ºC and 70ºC. Results showed significant interactions of temperature and coffee samples for coffee like attributes such as coffee identity, fidelity, and blended. The consumption temperature played a major impact on perceived flavor attributes of coffee and influenced Arabica, Blended and Robusta coffee differently and we have to consider that when blending coffees. Coffee identity and fidelity significantly increased with an increase in all temperatures, but most attributes showed significantly higher intensity only for samples served at 70ºC regardless of insignificant differences at 60ºC and 50ºC. Three coffee samples (light, medium, and dark roasted) were tasted with and without milk or sugar. The data were submitted to principal component analysis and cluster analysis. The first 2 PC’s allowed to separate coffee into three categories and CA revealed similar distribution of coffee into three clusters. Coffee like attributes were seemed to play a more important role in the determination of clusters as the addition of milk and sugar decreased the intensity of key flavor attributes such as coffee identity, bitterness, fidelity, roasted, blended, and longevity. The flavor attributes of dark roasted coffee was more impacted by the addition of milk and sugar. Results suggested that the effect of addition (milk and/or sugar) is correlated to the degree of roasting and we have to consider the milk and sugar additions according to degree of roasting.
Keywords: Coffee; Temperature; Milk; Sugar